1988
DOI: 10.1111/j.1600-0722.1988.tb01406.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial flora associated with presence of root surface caries in periodontally treated patients

Abstract: Emilson CG, Klock B, Sanford GB. Microbial flora associated with presence of root surface caries in periodontally treated patients. Scand J Dent Res 1988; 96: 40-9.Abstract -Examination of saliva and dentai plaqtie was carried out in 35 adults who had been treated for periodontal disease 3 yr earlier. Plaque samples were collected from approximal and btiiccal sound and carions root surfaces. The satnples were analyzed for the presence and proportions of members of Streptococcus, Lactobacillus and Actinomyces. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
43
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 30 publications
7
43
1
Order By: Relevance
“…in plaque from sound and exposed root surfaces or in infected dentine from carious lesions as, overall, they represented approximately 10% of the flora. These observations support those in previous reports [Emilson et al, 1988;Brown et al, 1986;Keltjens et al, 1987;Fure, 1987] that the proportions of A. naeslundii were not significantly different in plaque from sound and exposed root surfaces and carious lesions. The proportion of A. naeslundii found here is also very similar to the proportion (12.8 5.8%) reported by Schüpbach et al [1995].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…in plaque from sound and exposed root surfaces or in infected dentine from carious lesions as, overall, they represented approximately 10% of the flora. These observations support those in previous reports [Emilson et al, 1988;Brown et al, 1986;Keltjens et al, 1987;Fure, 1987] that the proportions of A. naeslundii were not significantly different in plaque from sound and exposed root surfaces and carious lesions. The proportion of A. naeslundii found here is also very similar to the proportion (12.8 5.8%) reported by Schüpbach et al [1995].…”
Section: Discussionsupporting
confidence: 83%
“…There are conflicting reports of the composition of the microflora associated with sound and diseased root surfaces; some studies [Brown et al, 1986;Keltjens et al, 1987] have found no significant difference between bacterial populations whereas others [Fure et al, 1987;Emilson et al, 1988] reThe Isolation of Actinomyces naeslundii from Sound Root Surfaces and Root Carious Lesions Caries Res 1998;32:100-106 101 ported significantly greater proportions of Actinomyces spp. and Streptococcus sanguis on sound and exposed root surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Since the present study was not undertaken to determine the composition of the plaque microflora sampled from sites with or without root surface lesions, as reported previously [Ellen et al" 1985b;Brown et al. 1986;Fure et al, 1987;Emilson et al. 1988], we cannot compare our results with others.…”
Section: Discussionmentioning
confidence: 50%
“…are associated with root surface caries [Ellen et al., 1985a, b;Brown et al. 1986; Fure et al, 1987; Keltjens et al., 1987;Emilson et al, 1988]. The main focus of these studies was to determine the composition of the plaque overlying the carious lesion and hence no attempts were made to localize specific microorganisms within the ca rious lesions.…”
mentioning
confidence: 99%
“…Mutans streptococci have been implicated in the etiology of human root surface caries, whereas there is no evidence of Actinomyces playing a significant role [Ellen et al, 1985;Brown et al, 1986;Keltjens et al, 1987;Fure et al, 1987;Emilson et al, 1988], Treat ment with chlorhexidine gel considerably reduces the number of mutans streptococci in plaque and saliva in subjects with high levels of these microorganisms [Emilson 1977a[Emilson , 1981Maltz et al, 1981;Schaeken et al, 1984Schaeken et al, , 1986. In most cases, however, the micro organisms reappear and reach pretreatment levels within 2-5 months.…”
mentioning
confidence: 99%